Angiotensin II receptor blockers following intravenous nicardipine administration to lower blood pressure in patients with hypertensive intracerebral hemorrhage: a prospective randomized study. Issue 1 (February 2017) - Inamasu, Joji; Nakae, Shunsuke; Adachi, Kazuhide; Hirose, Yuichi
Abstract : Background and objective: In patients with hypertensive intracerebral hemorrhage (HICH), intravenous nicardipine is primarily used to lower blood pressure (BP). However, there are few studies investigating the role of oral antihypertensives administered after intravenous nicardipine to prevent BP from rising. Angiotensin II receptor blockers (ARBs) may be beneficial in HICH patients not only as antihypertensives but also by lowering plasma catecholamine levels. A prospective randomized study was conducted between January 2015 and March 2016 to comparatively evaluate the efficacy of two ARBs (azilsartan vs. candesartan) following intravenous nicardipine administration on BP reduction. Patients and methods: Thirty conscious HICH patients presenting within 6 h of symptom onset were enrolled (15 in each arm). After administering intravenous nicardipine for 24–48 h, the patients were randomized either to the azilsartan (20 mg) arm or to the candesartan (8 mg) arm. Frequency of hematoma expansion, 30-day modified Rankin scale, and temporal profiles of systolic blood pressure (SBP) and plasma norepinephrine/aldosterone were compared. Results: Substantial hematoma expansion occurred in two (13%) azilsartan patients and in one (7%) candesartan patient ( P =1.00). SBPs were maintained at lower than 140±20 mmHg in both arms. Neither SBPs nor plasma norepinephrine/aldosterone levels differed significantly. All 30 patients had 30-day modified Rankin scale scores of 1–2. Conclusion: Administration of ARBs following intravenous nicardipine effectively prevented BP from rising in HICH patients. However, whether BP should be strictly managed after 24 h of symptom onset should be addressed in future studies focusing not only on neurologic but also on cardiovascular and renal functions of HICH patients.